Thermal and Non-Thermal Plasma for Destruction of Pollutants - Litter, Marta Irene (2021)
Wastewater remediation has become a global concern; thus, thedevelopment of innovative advanced oxidation processes (AOPs)for wastewater treatment is still a major challenge. Advanced oxidationprocesses (AOPs) are innovative tools that involve an introductionof energy (e.g., chemical, electrical and radiative) intothe reaction zone to generate highly reactive species, especiallyhydroxyl radicals (HO?). In this sense, plasma technology is includedamong AOPs and considered as a promising remediationtechnology for water remediation. Developed since 1987, thetechnique is environmentally friendly, simple and effective for decomposingtoxic organic compounds in raw water or wastewater. In view of these facts, applications of atmospheric pressureelectrical plasma technologies for water treatment attract the increasinginterest and emerge as technological opportunities for theplasma community.